Does media exposure relate to the illusion of knowing in the public understanding of climate change? - Yang, Xiaodong (2020)
By acknowledging that people are cognitive misers, this study proposes that people may rely on the illusion of knowing as cognitive devices for attitudinal or behavioral change, in addition to factual knowledge. Accordingly, this study shifted the focus of inquiry from assessing media effects in increasing factual knowledge to assessing how media consumption relates to the illusion of knowing. Using a nationally door-to-door survey in Singapore (N = 705), the results revealed that individuals' attention to media messages about climate change and elaboration of these messages were positively related to the illusion of knowing. Furthermore, elaboration had moderating effects on the relationship between media attention and the illusion of knowing. These findings suggest that media consumption of climate change messages could drive the illusion of knowing, which is speculated to account for pro-environmental behaviors in addressing climate change. Theoretical and practical implications were discussed.